The Role of Analytical Chemistry in Ensuring Food Safety and Methodological Bases of its Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article highlights the important role of analytical chemistry in the development of the chemical industry, and presents practical work carried out independently with students on quantitative and qualitative analysis of nutrients in food products, and the average values of the results obtained are presented in tables.